2001
DOI: 10.1300/j027v19n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dementia Care Through Community Linkages: A Multi-Site Demonstration Project

Abstract: The purpose of the multi-site project was to develop and implement a model for dementia care which improved linkages of caregivers to community services. Key components of the model included a single point of informational contact, provider education, case-finding, caregiver education and support, internal linkages, and linkages with community services. The model was implemented at six medical centers. Outcome measures included caregiver, provider, and community agency satisfaction. Caregivers reported high sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Our results showed that the reception of information, advice, and emotional support services increased the odds of being in the highly satisfied group. This is consistent with studies of i-18 caregiver satisfaction with medical care which have obtained lower satisfaction scores mainly in areas related to information exchange between health care professionals and caregivers (Haley et al, 1992;Jones & Lester, 1994;van Hout et al, 2001;Venohr et al, 2001;Wellwood et al, 1995). As well, having received services other than those usually listed as caregiver support services decreased the odds of being in the lower satisfaction group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that the reception of information, advice, and emotional support services increased the odds of being in the highly satisfied group. This is consistent with studies of i-18 caregiver satisfaction with medical care which have obtained lower satisfaction scores mainly in areas related to information exchange between health care professionals and caregivers (Haley et al, 1992;Jones & Lester, 1994;van Hout et al, 2001;Venohr et al, 2001;Wellwood et al, 1995). As well, having received services other than those usually listed as caregiver support services decreased the odds of being in the lower satisfaction group.…”
Section: Discussionsupporting
confidence: 90%
“…Areas that generally receive lower satisfaction scores in these studies are often related to information they received on diagnosis, course of illness or community services (Haley, Clair, & Saulsberry, 1992;van Hout, Vernooij-Dassen, Hoefnagels, & Grol, 2001;Venohr et al, 2001), or communication between hospital staff and the caregiver (Jones & Lester, 1994;Wellwood et al, 1995). Other variables that have demonstrated association with satisfaction with medical care in general are also identified as important control variables to include in any studies of satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Our cross-group analysis, however, indicates that poor information transfer contributes to poor service coordination. These findings are relevant to those of Powell Davies et al (2006) within the Australian context and others in wider contexts who have emphasised for over a decade the importance of having a coordinated, multidisciplinary system of dementia care (Jurkowski 1998, Venohr et al 2001, Fortinsky et al 2002, Cherry et al 2004, Coon et al 2004, Dröes et al 2005, Lemieux-Charles et al 2005, McCrystle & Menscer 2005Abendstern et al 2006, Vickrey et al 2006.…”
Section: Information Transferabilitysupporting
confidence: 56%
“…These findings are relevant to those of Powell Davies et al . (2006) within the Australian context and others in wider contexts who have emphasised for over a decade the importance of having a coordinated, multidisciplinary system of dementia care (Jurkowski 1998, Venohr et al . 2001, Fortinsky et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation